Land use/land cover change and its implication on soil erosion in an ecologically sensitive Himachal Himalayan watershed, Northern India - Prashanth, Manthena; Kumar, Arun; Dhar, Sunil; Verma, Omkar; Rai, Shashi Kant; Kouser, Beena (Frontiers in Forests and Global Change, 2023)
Soil erosion is a major environmental problem that affects land and water resources. It has many negative implications that lead to deforestation, poor agricultural practices, loss of soil fertility, and siltation that hinder socio-economic development. Given this the present study was conducted to estimate the soil loss about long term land use/land cover change (LULC) in the Dehar watershed, Himachal Himalaya, North India. The study was carried out using Landsat and Sentinel imageries of 1999, 2000, and 2020. GIS-based Revised Universal Soil Loss Equation (RUSLE) model was applied to know the potential soil risk. The parameters used as inputs for computing the spatiotemporal changes of soil loss were topographic, soil erodibility, rainfall erosivity, crop management, and conservation support practice factors. The results showed mean soil of 63.71, 60.99, and 66.71 t/ha/yr for the years 1999, 2010, and 2020, respectively, demonstrating that the LULC changes had influenced the soil losses in the Dehar watershed. Therefore urgent interventions are required with the involvement of scientists, policymakers, and the general public for the conservation and management of soil resources.